Obtenção e uso de carbon dots de glicerina na produção de solketal - Silva, Crislaurio Gonçalves da (2024)
In Brazil, especially in the Central-West region, there is a high production of biodiesel, and consequently large quantities of an impure co-product called glycerol. Due to the low utilization rate of this co-product resulting from its high level of impurities, commercial glycerin was chosen, which contains glycerol. Considering the large-scale production of biodiesel and consequently impure glycerol, it is necessary to find ways to utilize it. In this work, commercial glycerin was used as a precursor in the production of carbon dots (C-dots). The C-dots obtained through the transformation of glycerin were evaluated regarding their capacity to produce solketal. To obtain different types of C-dots, they were modified using functionalizing agents such as citric acid and urea. The produced C-dots were analyzed using UV-Vis spectroscopic techniques, FTIR, and PL, as well as thermal analytical techniques TG-DTA. The formation of C-dots obtained with the use of glycerin and functionalizing agents was confirmed by absorption bands between 220 – 270 nm in the UV-Vis spectra and light emission between 410 – 440 nm when excited at 360 nm. According to the FTIR spectra of the C-dots, the outermost region of the nanomaterials presents the groups -OH, -CH2, and C=O. Additionally, the presence of water and other molecules of lower molecular weight was observed in the TG-DTA curves of the product obtained. Characterization techniques indicated that the products still presented glycerin in their composition, forming a product containing a mixture of glycerin and C-dot. The use of this product in the synthesis of solketal showed the formation of up to 17.22% solketal, presenting a selectivity of 95.09%.